Aplikasi Edukasi Kuis Matematika Untuk Tingkat Sekolah Menengah Pertama Berbasis Android - Yulia Yulia; Very Karnadi (Politeknik Negeri Batam, 2020)
Mathematics is a science that is widely used in everyday life such as used in trade transactions, carpentry, and so on. But until now many people think that mathematics is a subject that is considered difficult and difficult to understand, especially for junior high school students. Though mathematics itself has been taught starting from the level of childhood and elementary school. Because learning methods still use conventional methods such as the ability to write and count, this is what makes students feel bored because moreover some students do not like these math subjects. Not only in terms of subjects and learning media is still conventional in nature that is only based on the book. For this reason, a learning media is created which is packaged in an android-based application by including elements of mathematics learning in it. The application that was designed was a junior high school level mathematics education quiz application, with the aim of training students 'ability to count, train their memory and increase students' interest in learning in mathematics.